MASTERING UBUNTU SERVER explore the versatile, powerful linux server... distribution ubuntu 22.04 with this comprehensive. - LaCroix, Jay (PACKT PUBLISHING LIMITED, 2022)
Your one-stop resource to learn, configure and use Ubuntu 22.04 for your day-to-day operations and deployments. Ubuntu Server is taking the server world by storm - and for a good reason! The server-focused spin of Ubuntu is a stable, flexible, and powerful enterprise-class distribution of Linux with a focus on running servers both small and large. Mastering Ubuntu Server is a book that will teach you everything you need to know in order to manage real Ubuntu-based servers in actual production deployments. This book will take you from initial installation to deploying production-ready solutions to empower your small office network, or even a full data center. You'll see examples of running an Ubuntu Server in the cloud, be walked through set up popular applications (such as Nextcloud), host your own websites, and deploy network resources such as DHCP, DNS, and others. You'll also see how to containerize applications via LXD to maximize efficiency and learn how to build Kubernetes clusters. This new fourth edition updates the popular book to cover Ubuntu 22.04 LTS, which takes advantage of the latest in Linux-based technologies. By the end of this Ubuntu book, you will have gained all the knowledge you need in order to work on real-life Ubuntu Server deployments and become an expert Ubuntu Server administrator who is well versed in its feature set.